Estudo dos componentes nutricionais e imunológicos na perda de peso em camundongos com alergia alimentar - Leticia Figueiredo Moreira (2006)
Allergic diseases have reached epidemic proportions and are characterized by IgE production against antigens that gain the organisms through the mucosas. Here, we used a allergy model which BALB/c mice receive ovalbumin orally after sensitization with ovalbumin. After the oral challenge with egg white solution, the ovalbumin sensitized BALB/c mice usually show intestinal modifications, with mucous production, edema, increased of the number of mast cells and eosinophils. Systemic signals are associated with antiovalbumin IgE productions and loss of body weight. In order to see whether or not the lost of the weight hadnutrituional or immunological mechanisms, we used balanced diets containing ovalbumin. The liophilization of the ovalbumin did not reduce its allergenicity, once ovalbumin sensitized BALB/c mice lost their weight after ingestion of natural egg white, liophilized egg white in water or liophilized ovalbumin inside the diet. The ingestion of ovalbumin diet after ovalbumin sensitization also caused intestinal mucous production and IgE production in both BALB/c and C57BL6 mice. , reduction of abdominal fat and increased of hepatic cholesterol n BALB/cmice. In BALB/c, the reduced body weight was associated with reduction of muscle mass and abdominal fat. There was general edema in ovalbumin sensitized C57BL6, and reduction of abdominal fat after ovalbumin diet consumption. Increased hepatic cholesterol concentration was find in both animals after ovalbumin ingestion. These results were not connected to TNFalpha production. Although much is still unknown about the etiology of cachexia in this allergy model, we suggest that this model reproduce clinical allergic situation in which multiple cytokines, neuropeptides, classic stress hormones, and intermediary substrate metabolism are involved.